Percutaneous cholecystostomy for biliary decompression in patients with cholangitis and pancreatitis. Issue 10 (October 2018) - Park, Jin Myung; Kang, Chang Don; Lee, Minjong; Park, Sung Chul; Lee, Sung Joon; Jeon, Yong Hwan; Cho, Seong Whi
Objective: This study was performed to assess the effectiveness and safety of percutaneous cholecystostomy (PC) for biliary decompression. Methods: We retrospectively analyzed our institution's PC database from March 2015 to August 2017 and selected patients with biliary obstruction. The primary outcomes were the technical and clinical success rates. As secondary outcomes, adverse events and pain after PC were compared with those of patients who underwent PC for acute cholecystitis during the same period. Results: Twenty patients underwent PC for biliary obstruction (cholangitis, 19; pancreatitis, 1). The technical and clinical success rates were 100%. The median serum total bilirubin level decreased considerably from 4.5 to 1.4 mg/dL after PC. An adverse event (catheter migration) occurred in 1 patient, and 17 patients developed pain after PC. During the same period, 104 patients underwent PC for cholecystitis. Adverse events occurred in 7 patients, and 62 developed pain. There was no significant difference in the adverse event rate between the cholangitis/pancreatitis and cholecystitis groups (5.0% vs. 6.7%, respectively), but pain occurred considerably more frequently in the cholangitis/pancreatitis group (94.4% vs. 63.9%, respectively). Conclusions: PC is an effective and safe method for biliary decompression in selected patients. However, attention should be paid to postoperative pain.